Implementasi Gaya Kepemimpinan Kepala Sekolah terhadap Kinerja Guru untuk Meningkatkan Kualitas Hasil Pembelajaran pada Sekolah Menengah Atas - Fikri indriana Somantri; Bakti Toni Endaryono (Da'watuna: Journal of Communication and Islamic Broadcasting, 2021)
This study aims to examine, disclose and obtain empirical evidence about the implementation of the principal's leadership style on improving teacher performance to improve the quality and learning outcomes. This research method uses descriptive qualitative methods with data collection techniques through interviews, field observations and documentation. The results of this study are the implementation of the principal's leadership style on teacher performance to improve the quality of learning with a democratic leadership style based on theological values. In improving teacher performance and the quality of learning, principals have program strategies including (a) teacher performance coaching strategies, (b) education staff discipline development, (c) teacher performance control and supervision, (d) motivation, (e) awarding and (f) Build teacher commitment.